2020
DOI: 10.18632/aging.103516
|View full text |Cite
|
Sign up to set email alerts
|

ASNEO: Identification of personalized alternative splicing based neoantigens with RNA-seq

Abstract: Cancer neoantigens have shown great potential in immunotherapy, while current software focuses on identifying neoantigens which are derived from SNVs, indels or gene fusions. Alternative splicing widely occurs in tumor samples and it has been proven to contribute to the generation of candidate neoantigens. Here we present ASNEO , which is an integrated computational pipeline for the identification of personalized Alternative Splicing based NEOantigens with RNA-seq. Our analyses showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Both RNA‐seq and WES data were available in Van Allen's melanoma cohort [23]. The processing results (including HLA, TMB, CYT) of the two melanoma cohorts were retrieved from our previous studies [25–27]. Chowell's melanoma cohort [9] contains 164 patients under anti‐CTLA4 treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Both RNA‐seq and WES data were available in Van Allen's melanoma cohort [23]. The processing results (including HLA, TMB, CYT) of the two melanoma cohorts were retrieved from our previous studies [25–27]. Chowell's melanoma cohort [9] contains 164 patients under anti‐CTLA4 treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, further studies are needed to ensure a full understanding of their mechanisms of action. Alternative splicing widely occurs in tumor samples and it has been proven to contribute to the generation of candidate neoantigens [ 15 ]. Here, we found that KIRC has shown a variety of specificities in alternative splicing.…”
Section: Resultsmentioning
confidence: 99%
“…Alternative splicing is an important mechanism in post-transcriptional regulation, and increasing evidences noted that alternative splicing is tightly associated with invasion and metastasis of cancer cells [ 14 ]. Alternative splicing is a rich source of tumor-specific neoantigen targets for immunotherapy [ 15 , 16 ]. It is worth noting that global changes in alternative splicing patterns also occur during the in vitro derivation of embryonic stem cells from the inner cell mass of blastocysts, suggesting that alternative splicing is not only progressing during the differentiation of stem cells, but also during the acquisition of stemness features in cancer stem cells [ 17 ].…”
Section: Backgroudmentioning
confidence: 99%
“…The Cm has potential clinical applications, including vaccine target detection and prediction of therapeutic effects of immune checkpoint inhibitors that have been reported to be associated with the degree of tumor mutation burdens. 7,8 Although we focused on SNV in the present study, several software programs for predicting neoantigens derived from fusion genes 61 and alternative splice events 62,63 have been developed using RNA-seq data. These variants are known to be an important source of potentially immunogenic neoantigens; [64][65][66] therefore, further utilization of RNA-seq data in addition to Cm may provide a comprehensive landscape of immunogenic neoantigens.…”
Section: Discussionmentioning
confidence: 99%